IMPROVING STUDENTS’ READING COMPREHENSION THROUGH PREVIEW, BRAINSTORM, PREDICT (PBP) STRATEGY - nur aisyah zulkifli (Al-Manar : English and Arabic Journal, 2014)
Reading helps students to improve their knowledge, experience, and to get much information from the written materials. It is also a skill that can make students develop their ways to learn well about something. By reading, the students can spend their time in good way to get information, knowledge, as well as enrich their vocabulary, and improve their structure. On the other hand, there some students who cannot get the point about what they read. Therefore, it is a job of the lecturer/teacher to solve that problem, how to improve students low comprehension by using strategy or technique. In this paper, the writer want to explain about how to improve students reading comprehension by using Preview, Brainstorm, Predict (PBP) strategy. Preview, Brainstorm, Predict (PBP) strategy is part of pre reading. It refers to a positive pre-reading with simply model the process of previewing the text by looking at the title, author, subheadings illustrations and other relevant structures. This strategy is a strategy that engages students to preview the text by reading that can be implemented with little preparation.